Mother Tongue based Multilingual Education (MT- MLE): Teachers’ Language Ideologies - Paudel, Jnanu Raj (Journal of NELTA Surkhet, 2018)
Mother Tongue based Multilingual Education (MT- MLE) is a form of multilingual education built on the learners’ mother tongue. This article explores the teachers’ ideology on the policy (as policy appropriator). The ideologies of the language teachers have been drawn from the interpretive perspectives where the reality is judged based on the experiences of the research and the researched. The participants in this study covered five English language teachers who have been working in the area of multilingualism. The in-depth interview with them supplied the data for arriving into the results and conclusions. Finally, the teachers unraveled their strong belief on the use of MLE for language promotion and protection of indigenous knowledge. Journal of NELTA Surkhet Vol. 5 January, 2018, Page: 28-40